Interaction effects between smoking and internet gaming disorder on resting-state functional connectivity of the ventral tegmental area and hippocampus - Qiu, Xianxin; Han, Xu; Wang, Yao; Ding, Weina; Sun, Yawen; Lei, Hao; Zhou, Yan; Lin, Fuchun (Frontiers in Neuroscience, 2023)
Background: Many reports indicated cigarette smoking and internet gaming disorder (IGD) with widespread alterations of resting-state functional connectivity (rsFC) in the reward and memory circuits, respectively. Epidemiological studies have also shown high comorbidity of cigarette smoking and IGD. However, the underlying mechanisms are still unknown. Therefore, we investigated the comorbidity and interaction effects between smoking and IGD from the rsFC perspective. Methods: Resting-state functional magnetic imaging data were collected from 60 healthy controls (HC), 46 smokers, 38 IGD individuals and 34 IGD comorbid with smoking (IGDsm) participants. Voxel-wise rsFC maps were calculated for all subjects with the ventral tegmental area, rostral hippocampus and caudal hippocampus as regions of interest, respectively. Results: Significant interaction effects between smoking and IGD were mainly involved in the reward and memory circuits, that is, the rsFC between the ventral tegmental area and right nucleus accumbens, between the rostral hippocampus and bilateral nucleus accumbens, sensorimotor areas as well as left middle temporal gyrus. Specifically, in these circuits, smokers showed decreased rsFC than HC group while IGDsm showed increased rsFC than smokers as well as IGD individuals. IGDsm and HC groups showed no significant difference. The altered rsFC were also correlated with clinical measures. Conclusions: These findings indicate that the reduced rsFC affected by smoking or IGD increases under the effect of another type of addiction such as smoking and IGD, but only increases to the normal state, which might explain the comorbidity and interaction between smoking and IGD from the perspective of functional circuits.